Optimalisasi Penataan Fasilitas Wisata Danau Sendang Cinta Di Battu Winangun - Lucyana Lucyana; Eka Rizki Meiwinda; Destiarini Destiarini; Azwar Azwar; Abdul Rahman (Universitas Dehasen Bengkulu, 2023)
Tourism has the economic potential to support regional income. One of the natural resources located in Battu Winangun Village is the water area, namely Lake Sendang Cinta. The method used in this service is the method of observation, interviews and outreach. The concept of optimizing the Sendang Cinta Lake area is by building parking facilities, toilets, places to eat, parks, main gates, and wharves and tourism development in an area that involves the participation of community members in tourism development plans, which makes the area have certain characteristics and play a role major in this activity.